Neurocognitive function in children with cochlear implants and hearing aids: a systematic review - Lima, Jefferson Vilela da Silva; de Morais, Caroline Favaretto Martins; Zamberlan-Amorim, Nelma Ellen; Mandrá, Patricia Pupin; Reis, Ana Cláudia Mirândola Barbosa (Frontiers in Neuroscience, 2023)
Purpose: To systematically review the existing literature that examines the relationship between cognition, hearing, and language in children using cochlear implants and hearing aids. Method: The review has been registered in Prospero (Registration: CRD 42020203974). The review was based on the Preferred Reporting Items for Systematic Reviews and Meta-Analysis and examined the scientific literature in VHL, MEDLINE, CINAHL, Scopus, WOS, and Embase. It included original observational studies in children using hearing aids and/or cochlear implants who underwent cognitive and auditory and/or language tests. Data were extracted from the studies and their level of evidence was graded with the Oxford Center for Evidence-Based Medicine: Levels of Evidence. Meta-analysis could not be performed due to data heterogeneity. Outcomes are described in narrative and tables synthesis. Results: The systematic search and subsequent full-text evaluation identified 21 studies, conducted in 10 different countries. Altogether, their samples comprised 1,098 individuals, aged 0.16 to 12.6 years. The studies assessed the following cognitive domains: memory, nonverbal cognition, reasoning, attention, executive functions, language, perceptual-motor function, visuoconstructive ability, processing speed, and phonological processing/phonological memory. Children with hearing loss using cochlear implants and hearing aids scored significantly lower in many cognitive functions than normal hearing (NH) children. Neurocognitive functions were correlated with hearing and language outcomes. Conclusion: Many cognitive tools were used to assess cognitive function in children with hearing devices. Results suggest that children with cochlear implants and hearing aids have cognitive deficits; these outcomes are mainly correlated with vocabulary. This study highlights the need to understand children's cognitive function and increase the knowledge of the relationship between cognition, language, and hearing in children using cochlear implants and hearing aids.